Stuart at the Library - Hill, Susan; Nang ChanYeema (New York, USA HarperCollins Publisher, Inc., 2001)
At first Stuart is afraid of Bookworm the library owl, but they become friends when Stuart says he will help Bookworm learn to read.
Keywords: Level Books